Estimation of the value of regional ecosystem services of an archipelago using satellite remote sensing technology: A case study of Zhoushan Archipelago, China - Liyan Wang; Chao Chen; Fang Xie; Zijun Hu; Zili Zhang; Huixin Chen; Xinyue He; Yanli Chu (International Journal of Applied Earth Observations and Geoinformation, 2021)
Ecosystem functions and services support all life on earth and are directly or indirectly related to human well-being. Meanwhile, island cities have concentrated populations, limited natural resources, and fragile environments. This study obtained land use and cover change information for an island city based on long-term series remote sensing imagery. Then, ecosystem services value was estimated based on the equivalent factor method. Finally, the correlations between ecosystem service values and social-economic indicators were analyzed. The results showed that: (1) From 1984 to 2017, land-use patterns changed significantly in Zhoushan City. The spatial extent of urbanized land increased, vegetation and bare land area decreased, and water body areas initially increased, then decreased, and later increased. This reflects the fact that the aquaculture industry of Zhoushan was developing rapidly during the study period, and the process of urbanization and coastal port development was accelerating. (2) The total value of ecosystem services in the study area increased from 1,876.04 million yuan in 1984 to 2,128.52 million yuan in 2017 (+13.46%) with an average annual increase of 7.65 million yuan or 0.40% annually. The ecosystem service values of water conservation and waste disposal have changed significantly, both increasing by about 40%. (3) The value of ecosystem services was positively correlated with the areas of vegetation and water, while negatively correlated with the area of bare land. This study not only provides a reference for the sustainable use of regional land resources but also establishes a new method of regional environmental assessment, which is of great significance for the formulation of sustainable development planning.